1996
DOI: 10.1042/bj3160999
|View full text |Cite
|
Sign up to set email alerts
|

Albumin binding of unconjugated [3H]bilirubin and its uptake by rat liver basolateral plasma membrane vesicles

Abstract: Using highly purified unconjugated [3H]bilirubin (UCB), we measured UCB binding to delipidated human serum albumin (HSA) and its uptake by basolateral rat liver plasma membrane vesicles, in both the absence and presence of an inside-positive membrane potential. Free UCB concentrations ([Bf]) were calculated from UCB-HSA affinity constants (K'f), determined by five cycles of ultrafiltration through a Centricon-10 device (Amicon) of the same solutions used in the uptake studies. At HSA concentrations from 12 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…Because Ͼ99.8% of bilirubin was bound at all albumin concentrations studied, bound and total bilirubin concentrations are considered identical for modeling purposes. (5). This discrepancy probably reflects higher levels of unbound impurities in our earlier study because of exchange of tritium with the solvent.…”
Section: Table I Estimates Of Impurity Levels and Formation Rates Usicontrasting
confidence: 37%
See 2 more Smart Citations
“…Because Ͼ99.8% of bilirubin was bound at all albumin concentrations studied, bound and total bilirubin concentrations are considered identical for modeling purposes. (5). This discrepancy probably reflects higher levels of unbound impurities in our earlier study because of exchange of tritium with the solvent.…”
Section: Table I Estimates Of Impurity Levels and Formation Rates Usicontrasting
confidence: 37%
“…Preparation of Stock [ 14 C]Bilirubin-Radiolabeled bilirubin conjugates were purified from bile after intravenous infusion of ␦- [5][6][7][8][9][10][11][12][13][14] C]aminolevulinic acid (PerkinElmer Life Sciences, Boston, MA) to bile-fistula rats using a protocol approved by the Animal Committee of Northwestern University Medical School and the Chicago VA Lakeside Medical Center. Purified 14 C-unconjugated bilirubin was then obtained by a modification of the method of Ostrow et al (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [$H]bilirubin was made by the Wilzbach procedure, which involves exposure of unlabelled bilirubin to $H gas at high pressure for 3 weeks. This procedure was first used to prepare [$H]bilirubin by Grodsky et al [2], whose work was not cited in the paper and who found that it caused significant decomposition of bilirubin. The decomposition and other reactions that occur during the Wilzbach treatment of bilirubin are unknown, but are likely to involve free-radical processes, disproportionation to non-IXα isomers, and addition to double bonds [3][4][5][6].…”
Section: Binding Of [ 3 H]bilirubin To Albumin and Plasma Membrane Vementioning
confidence: 99%
“…For example, a high expression rate is not a guarantee that a corresponding high number of positive clones will be obtained, and cases have been reported of successful screening of a library prepared from a weakly expressing tissue [1]. Furthermore, particular mRNAs are difficult to reverse-transcribe, possibly owing to a high CG content or base-paired structures, leading to an under-representation of the desired cDNA clone in the library, CG-rich sequences generally behave problematically in polymerase reactions, even at elevated temperatures (72 mC), and several attempts have been made to solve these problems [2,3].…”
mentioning
confidence: 99%